Income taxation in an empirical collective household labour supply model with discrete hours - Hans G. Bloemen (Institute for the Study of Labor (IZA), 2010)
Most empirical studies on the impact of labour income taxation on the labour supply behaviour of households use a unitary modelling approach. In this paper we empirically analyze income taxation and the choice of working hours by combining the collective approach for household behaviour and the discrete hours choice framework with fixed costs of work. We identify the sharing rule parameters with data on working hours of both the husband and the wife within a couple. Parameter estimates are used to evaluate various model outcomes, like the wage elasticities of labour supply and the impacts of wage changes on the income sharing between husband and wife. We also simulate the consequences of a policy change in the tax system. We find that the collective model has different empirical outcomes of income sharing than a restricted model that imposes pooling of men's earnings and the household's non-labour income in the female's budget constraint. These differences in outcomes have consequences for the evaluation of a policy change in the tax system.
Keywords: J22; 330; Labour supply; household behaviour; collective model; taxation; Einkommensteuer; Arbeitsangebot; Privater Haushalt; Arbeitszeit; Diskrete Entscheidung; Erwerbstätigkeit; Steuerwirkung; Schätzung; Niederlande